Recent Research of NiCo2O4/Carbon Composites for Supercapacitors - Xu, Junming; Shi, Yang; Cheng, Jipeng; Wang, Xinchang (Surfaces (Basel), 2022)
Supercapacitors have played an important role in electrochemical energy storage. Recently, researchers have found many effective methods to improve electrode materials with more robust performances through the increasing volume of scientific publications in this field. Though nickel cobaltite (NiCo2O4), as a promising electrode material, has substantially demonstrated potential properties for supercapacitors, its composites usually show much better performances than the pristine NiCo2O4. The combination of carbon-based materials and NiCo2O4 has been implemented recently due to the dual mechanisms for energy storage and the unique advantages of carbon materials. In this paper, we review the recent research on the hybrids of NiCo2O4 and carbon nanomaterials for supercapacitors. Typically, we focused on the reports related to the composites containing graphene (or reduced graphene oxide), carbon nanotubes, and amorphous carbon, as well as the major synthesis routes and electrochemical performances. Finally, the prospect for the future work is also discussed.